METAPHORICAL THINKING AND THE PROBLEM OF (UN)TRANSLATABILITY - Bevz, N. V. (The Journal of V. N. Karazin Kharkiv National University, Series Philosophy. Philosophical Peripeteias, 2017)
The phenomenon of immanence of some knowledge about the properties of the world determines the primary «metaphoric» of human thinking, which is expressed in language. Appeal to this phenomenon is necessary to find a positive basis for the theory and practice of translation. The general conceptual spectrum of postmodern philosophy can not provide such a basis. An analysis of the texts of Jacques Derrida and Walter Benjamin shows that there is no general positive metalinguistic foundation in the mindset of these thinkers. According to Derrida, the signified appears in the form of a «constitutive loss». For Benjamin, the universal basis of real languages is a kind of mystical fiction. But without the positive general basis, there is no room for a real translation. From the point of view of Benjamin and Derrida, language is not a reservoir of meanings, but a field of their incessant creation. However, in the absence of a single positive foundation, this position inspires a potentially endless and extremely free «reconstruction» of the author’s intention. Therefore, the objective results of modern sciences, which study language and thinking, should prevent unjustifiably broad speculation on the problem of untranslatability. The information available at our disposal on the nature of the work of the «mental apparatus» of human and the features of the functioning of sign systems allow one to effectively correct the speculative incontinence of certain philosophical developments in the problematics of translation.